Role of Counseling in Employee Performance in Public Universities(A Case Study of Kenyatta University) - Matolo, Rose Syombua; Mukulu, Elegwa (My University, 2016)
In order to achieve the set goals or perform the activities of any organization, employees have to be taken care of economically, politically and socially, to enable them perform to the standards required. One way of taking care of the employees is through workplace counseling. The paper aimed at investigating the role counseling plays in employee performance in public universities and it focused on Kenyatta University as a case in Kenya. The study population comprised of management staff, counselors, teaching and non-teaching members of staff. In order for the objectives of the study to be achieved, a questionnaire was used and data was collected and analyzed using SPSS. The research employed descriptive statistics which gave a result that there was a positive link between counseling and employee performance in public universities in Kenya
Keywords: Employee counseling; Employee performance; Human Resource Management; Public Universities in Kenya